Genome-wide analysis of the CCCH zinc finger gene family in pineapple (Ananas comosus L.) and their involvement in fruit development and translucency - Zhuanying Yang; Wenhao Jiang; Lidan Wang; Dongbo Lin (BMC Plant Biology)
Abstract Background Pineapple (Ananas comosus L.), an important tropical fruit with global significance, encounters ongoing difficulties in maintaining commercial quality due to fruit translucency. However, the molecular mechanisms underlying fruit translucency remain poorly characterized. Results In this study, we explored the CCCH zinc finger (CCCH-ZF) gene family, recognized for its regulatory functions in plant development and stress response, as a potential factor influencing translucency in pineapple. We performed a comprehensive genome-wide analysis, identifying 40 CCCH-ZF genes (AcC3H1-AcC3H40) categorized into nine phylogenetic groups. Structural analysis revealed conserved CCCH domains and diverse gene architectures, most of which included introns. Cis-regulatory element prediction indicated the presence of hormone-responsive motifs (ABA, GA, SA, IAA, MeJA) and growth-related elements, suggesting complex regulatory roles. Expression profiling showed tissue-specific expression patterns, with eight genes predominantly expressed in floral organs. During fruit development, AcC3H10/14/31 exhibited peak expression at later stages, while AcC3H2/5 showed a decline. Notably, twelve genes (e.g., AcC3H7/9/11) were upregulated during late-stage translucency, whereas four (e.g., AcC3H1/8) were downregulated. Subcellular localization suggested nuclear targeting for eight proteins (e.g., AcC3H4/8-YFP) and plasma membrane localization for AcC3H2/16-YFP, indicating functional diversification. These findings present insights into the structural, evolutionary, and spatial characteristics of pineapple CCCH-ZF genes and highlight their potential roles in fruit development and translucency. Conclusion This study establishes a foundation for future functional analyses to elucidate the molecular mechanisms governing pineapple fruit quality and postharvest physiology.